Technical books for extension service and farmers to improve fertility and pest management of upland cropping systems in Madagascar - CGIAR Research Program on Rice (2020)
Multi-year experiments and diagnosis contributed to a decision tool for extension service and farmers to improve fertility and pest management of upland cropping systems, First technical books were achieved in Malagasy and French under the umbrella of the SECURE project focused from 2017 to 2021 on rice farming systems https://www.secure.mg/.